2017
DOI: 10.3390/ijms18071458
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab-Based Chemotherapy Combined with Regional Deep Capacitive Hyperthermia in Metastatic Cancer Patients: A Pilot Study

Abstract: Abstract:As an angiogenesis inhibitor, bevacizumab has been investigated in combination with different chemotherapeutic agents, achieving an established role for metastatic cancer treatment. However, potential synergic anti-angiogenic effects of hyperthermia have not tested to date in literature. The aim of our study was to analyze efficacy, safety, and survival of anti-angiogenic-based chemotherapy associated to regional deep capacitive hyperthermia (HT) in metastatic cancer patients. Twenty-three patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our data demonstrated that DEHY may enhance the bevacizumab-based treatment, in particular improving tumor response (78).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our data demonstrated that DEHY may enhance the bevacizumab-based treatment, in particular improving tumor response (78).…”
Section: Discussionmentioning
confidence: 53%
“…To the best of our knowledge, scientific literature offers very few data on the efficacy of anti-angiogenetic agents plus chemotherapy combined with HT (78).…”
Section: Introductionmentioning
confidence: 99%
“…mEHT is applied together with conventional modalities like chemo, radio or immunotherapy to enhance their effect and tumor-specificity [ 3 ]. mEHT can also boost the effect of targeted therapies, e.g., angiogenesis inhibition by Bevacizumab (Avastin ® ) in different types of malignancies, including breast cancer [ 4 ]. Hyperthermia decreases the activity of hypoxia-inducible factor 1 (HIF-1) and contributes to the vascular endothelial growth factor (VEGF)-mediated angiogenesis inhibition of Bevacizumab [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of paclitaxel >20 years ago for the treatment of epithelial ovarian cancer (EOC), only a few phase III trials testing other therapeutic agents have demonstrated notable data in terms of clinical outcome (1). Two studies demonstrated an increase in progression-free survival (PFS) time and, in a selected subgroup of patients, overall survival (OS) time (2) or only in PFS time (3), with the introduction of the anti-vascular endothelial growth factor (VEGF) monoclonal antibody, bevacizumab, using a therapeutic schedule based on paclitaxel (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%